Implementation of Swallow Cultivation Tax in Indonesia - Yusriadi Yusriadi (Universitas Negeri Medan, 2019)
Tax is one of the sources of state revenue used to carry out development for all the people of Indonesia. One of the implementations of the tax policy is swallowing cultivation. Swallow nest business is indeed a business that can bring in a decent income. Qualitative methods used in the form of library research, data collection obtained through journals, books, magazines, documents, and the web that are relevant to an investigation — data analysis techniques based on library data on the implementation of taxes on swallow cultivation in Indonesia. Assessment is carried out by looking at the implementation of the tax collection (results, costs, ease of application) with standard taxation criteria. These criteria are related to the adequacy, equity, and convenience.